Continuity in transition: Combining recovery and day-of-week perspectives to understand changes in employee energy across the 7-day0.167emweek - Oliver Weigelt; Katja Siestrup; Roman Prem (Journal of Organizational Behavior, 2021)
We integrate perspectives from research on recovery from work and perspectives from day-of-week research to predict continuous as well as discontinuous changes in vitality and fatigue. We examine whether changes in recovery experiences and sleep quality predict changes in human energy over the course of the weekend. Furthermore, we consider positive anticipation of work at the start of the workweek and effort during the workweek to predict changes in energy. We collected experience sampling data from 87 employees over the course of 120.167emdays. In total, 2,187 observations nested in 9720.167emdays were eligible for analysis. Applying discontinuous growth curve modeling, we found that human energy increases continuously during the weekend, drops on Monday, follows a passageway trajectory from Monday to Thursday, and increases on Friday again. Changes in recovery experiences did not predict changes in energy but increases in sleep quality did. Positive anticipation of work attenuated the drop in vitality on Monday. Effort did not predict changes in energy over the course of the workweek. Our results suggest that the transition between weekends and workweeks and vice versa accounts for considerable changes in human energy and that weekends are recuperative, particularly because they provide the opportunity for better sleep.
Keywords: 650; day-of-week; effort-recovery model; human energy; weekend recovery